Simultaneous determination of some food additives in soft drinks and other liquid foods by flow injection on-line dialysis coupled to high performance liquid chromatography - Orawan Kritsunankul (2018)
Flow injection on-line dialysis was developed for sample pretreatment prior to the simultaneous determination of some food additives by high performance liquid chromatography (FID-HPLC). A liquid sample or mixed standard solution (900 μL) was injected into a donor stream (5%, w/v, sucrose) of FID system and was pushed further through a dialysis cell, while an acceptor solution (0.025 mol L-1phosphate buffer, pH 3.75) was held in the opposite side of the dialysis membrane. The dialysate was then flowed to an injection loop of the HPLC valve, where it was further injected into the HPLC system and analyzed under isocratic reverse-phase HPLC conditions and UV detection (230 nm). The order of elution of five food additives was acesulfame-K, saccharin, caffeine, benzoic acid and sorbic acid, respectively, with the analysis time of 14 min. On-line dialysis and HPLC analysis could be performed in parallel, providing sample throughput of 4.3 h-1. Dialysis efficiencies of five food additives were in ranges of 5-11%. Linear calibration graphs were in ranges of 10-100 mg L-1for acesulfame-K and saccharin, 10-250 mg L-1for benzoic acid and 10-500 mg L-1for caffeine and sorbic acid. Good precisions (RSD < 5%) for all the additives were obtained. The proposed system was applied to soft drink and other liquid food samples. Acceptable percentage recoveries could be obtained by appropriate dilution of the sample before injecting into the system. The developed system has advantages of high degrees of automation for sample pretreatment, i.e., on-line sample separation and dilution and low consumption of chemicals and materials. © 2011 Elsevier B.V. All rights reserved.